HUBUNGAN ANTARA GRADE HIPERTENSI DENGAN TINGKAT KEMANDIRIAN LANSIA DALAM ACTIVITIES OF DAILY LIVING (ADL) - Diana H. Soebyakto; Riko Sandra Putra; Nurjannah (LPPM STIKes Mitra Adiguna, 2024)
Based on data from the World Health Organization (WHO), in 2014 there were around 600 million hypertension sufferers throughout the world. For elderly people who suffer from hypertension, the higher the grade of hypertension, the higher the level of dependence of the elderly on their care giver, which in this case is the family in a community setting. The aim of the research was to determine the relationship between the grade of hypertension and the level of independence of the elderly in Activities of Daily Living (ADL) at the Harapan Kita Palembang Elderly Social Home in 2023. The research method used was quantitative analysis with a cross section approach. The population in this study were all elderly people who experienced hypertension at the Harapan Kita Social Home in Palembang with a total sample of 35 respondents taken using the purposive sampling method. The frequency distribution of the elderly's independence in Activities of Daily Living (ADL) is mostly independent, with 15 respondents (42.9%), the frequency distribution of the majority of the elderly experiencing stage 1 hypertension, 16 respondents (45.7%). The statistical test results showed that there was a relationship between the grade of hypertension and the independence of the elderly in activities of daily living /ADL at the Harapan Kita Palembang Elderly Social Home in 2023 with p.value = 0.025. The suggestion is that health workers can carry out routine blood tests on all elderly people so that their blood pressure can always be monitored, apart from that, officers can also get older people used to carrying out their daily activities without having to be helped so that they can increase the level of independence of elderly people, especially elderly people who suffer from hypertension.